ANALISIS KEPUASAN PENGGUNA TERHADAP WEBSITE PORTALSIA BERDASARKAN MODEL WEBQUAL 4.0 - Muhammad Alvin Nurrahman; Muhammad Irwan Padli Nasution (Departement Information Systems Universitas Kebangsaan Republik Indonesia, 2025)
The purpose of this study is to apply the WebQual 4.0 technique to assess user satisfaction with the academic PortalSIA UINSU website. In addition to a measurement for overall user satisfaction, the study concentrates on the three main components of the framework: usability, information quality, and service interaction quality. 24 enrolled students in the Information Systems study program were given a survey as part of a quantitative descriptive approach. The results indicate that while overall User Satisfaction scored 3.71 (Good), the scores for the underlying quality dimensions were mixed. Usability received a score of 3.51 (Good), and Information Quality scored 3.36 (Fair). The lowest score was for Service Interaction Quality at 2.92 (Fair), identifying it as the primary area of concern. Key issues contributing to this include slow system speed, delays in academic data updates (such as grades and GPA), and the absence of a direct feedback mechanism. The study concludes that the PortalSIA website is generally accepted but requires significant improvements in technical responsiveness and user communication channels to enhance the user experience fully. The findings demonstrate the effectiveness of the WebQual 4.0 model in providing a structured and objective assessment for evaluating web-based academic systems.